Enterprise risk management : guidance for practical implementation and assessment. - Hardy, Karen, 1962- (American Institute of Certified Public Accountants, Inc., 2014)
This publication includes invaluable guidance for anyone responsible for or advising on an enterprise risk management process (ERM), whether the process is in its early stages or is already well established. This resource will help you ensure the ERM process is well designed, well executed, and ultimately successful. Global, economic, and regulatory conditions as well as everyday internal risks can affect business operations, so it’s important to have a process in place that identifies these events and manages risks. This guide leverages the concepts of existing frameworks as a foundation for providing illustrative examples, best practices, and guidance for implementing or assessing an enterprise risk management process. - Resumé vydavatel